ANALISIS FAKTOR TINDAKAN IBU DALAM PEMBERIAN NUTRISI PADA BALITA DENGAN GIZI BURUK - Ade Sugih Herlambang; Yuni Sufyanti Arief; Ilya Krisnana (Universitas Airlangga, 2014)
Malnutritioan is a condition of chronic lack of nutrition. Malnutrition is a major health problem faced in many developingcountries. The Lack of nutrition in children can be caused by the attitude or behavior of the mother which is the factor inthe selection of improper feeding. The food selections, adequate availability of the food and food diversities influenced bythe mother’s level of knowledge about meals and nutritions.The objective of this research was to perceivedrelation between predisposing factors adn reinforcing factors that related to mother’s action in giving nutrition tochildren with malnutrition. This research used cross sectional design. The population was 22 mothers which has achildren between 1-3 years old with malnutrition. Data were collected by using a questionnaire an interview with therespondents. Data were the anakyzed using spearmen’s rho test with level of significance of <0,05. The resultshowed that between predisposing factors (Attitude, education level, knowledge) and reinforcing factors (health servicesupport and family support), knowledge level had possitive correlation with mother’s action in giving nutrition tochildren with malnutrition (p=0,01, r=0,656), education level also had possitive correlation with mother’s action ingiving nutrition to children with malnutrition (p=0,35, r=0,452), and the knowledge was the most dominant factors that hadpossitive correlation with mother”s action in giving nutrition to children with malnutrition. It can be concluded thatthe knowledge an educational level can influenced mother’s action in givin nutritions to children with malnutrition.Increase mother’s aspect in knowledge can be used to improve the possitive attitude in giving nutritions tomalnutritions children. Health promotion about malnutritions with the malnutrition mother’s as main targets can beused as alternative ways to improve mother’s knowledge.